Halimanes and cancer: ent-halimic acid as a starting material for the synthesis of antitumor drugs - Roncero, Alejandro M.; Tobal, Ignacio E.; Moro, Rosalina F.; Diez, David; Marcos, Isidro S. (Frontiers in Chemistry, 2023)
The development of new anti-cancer agents is an urgent necessity nowadays as is one of the major causes of mortality worldwide. Many drugs currently used are derived from natural products. Halimanes are a class of bicyclic diterpenoids present in various plants and microorganisms. Many of them exhibit biological activities such as antitumor, antimicrobial or anti-inflammatory. Among them, ent-halimic acid is an easily accesible compound, in big quantities, form the ethyl acetate extract of the plant Halimium viscosum, and it has been used as starting material in a number of synthesis of bioactive molecules. In this work, we review all the natural halimanes with antitumor and related activities until date, as well as the synthesis of antitumor compounds using ent-halimic acid as starting material.